Social Norms, Labour Market Opportunities, and the Marriage Gap Between Skilled and Unskilled Women. (30th December 2020) - Bertrand, Marianne; Cortes, Patricia; Olivetti, Claudia; Pan, Jessica
Abstract: In most of the developed world, skilled women marry at a lower rate than less skilled ones. We document heterogeneity across countries in how the marriage gap between skilled and unskilled women has evolved over time. As labour market opportunities for women have improved, the marriage gap has been growing in some countries but shrinking in others. We discuss the comparative statics of a theoretical model in which the (negative) social attitudes toward working women might contribute to the relatively lower marriage rate of skilled women and might also induce a non-monotonic relationship between their labour market prospects and their marriage outcomes. The model delivers predictions about how the skilled–unskilled marriage gap should react to changes in labour market opportunities across economies with more or less conservative attitudes toward working women. We verify the key predictions of this model in a panel of 26 developed countries, as well as in a panel of U.S. states.